1995
DOI: 10.1002/pi.1995.210370406
|View full text |Cite
|
Sign up to set email alerts
|

H‐complex formation and influence on the radical copolymerization of acrylic acid and 1‐vinyl‐2‐pyrrolidone in tetrahydrofuran

Abstract: The association constant of the H-complex formation between acrylic acid and 1-vinyl-2-pyrrolidone in tetrahydrofuran at 22°C ( K , = 1350moll-') was determined by means of 'H NMR spectroscopy. A detailed equation for the copolymer composition, accounting for the participation in the chain propagation of the above complex and that between acid and solvent molecules, was derived. It was used for evalution of the relative reactivities of the complexes discussed and of the uncomplexed 1 -vinyl-2-pyrrolidone molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2000
2000

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In previous papers 16,18,19 devoted to that monomer couple, the solvent effect on the formation of monomer complexes and on the copolymerization process has been proved and taken into account in the proposed copolymerization model. It has been demonstrated that the chain propagation steps involve monomer complexes.…”
Section: ±12mentioning
confidence: 97%
“…In previous papers 16,18,19 devoted to that monomer couple, the solvent effect on the formation of monomer complexes and on the copolymerization process has been proved and taken into account in the proposed copolymerization model. It has been demonstrated that the chain propagation steps involve monomer complexes.…”
Section: ±12mentioning
confidence: 97%
“…The associated transitions introduced above (eqns (25) for the state 00*, eqns (26) for the state 10*, eqns (27) for the state 01* and eqns (28) for the state 11*) allow us to describe the macromolecular propagation by a regular Markov chain 7,8 with the following transition matrix:…”
Section: 40mentioning
confidence: 99%
“…where : Complex model : K is the stability constant of the comonomer complex, [1] and [2] are the concentrations of the free monomers 1 and 2.…”
Section: Introductionmentioning
confidence: 99%